Advances in carbon management technologies : biomass utilization, manufacturing, and electricity management. Volume 2 - Sikdar, Subhas K.; Princiotta, Frank (Boca Raton : CRC Press, 2021)
Volume 2 of Advances in Carbon Management Technologies has 21 chapters. It presents the introductory chapter again, for framing the challenges that confront the proposed solutions discussed in this volume. Section 4 presents various ways biomass and biomass wastes can be manipulated to provide a low-carbon footprint of the generation of power, heat and co-products, and of recovery and reuse of biomass wastes for beneficial purposes. Section 5 provides potential carbon management solutions in urban and manufacturing environments. This section also provides state-of the-art of battery technologies for the transportation sector. The chapters in section 6 deals with electricity and the grid, and how decarbonization can be practiced in the electricity sector. The overall topic of advances in carbon management is too broad to be covered in a book of this size. It was not intended to cover every possible aspect that is relevant to the topic. Attempts were made, however, to highlight the most important issues of decarbonization from technological viewpoints. Over the years carbon intensity of products and processes has decreased, but the proportion of energy derived from fossil fuels has been stubornly stuck at about 80%. This has occurred despite very rapid development of renewable fuels, because at the same time the use of fossil fuels has also increased. Thus, the challenges are truly daunting. It is hoped that the technology choices provided here will show the myriad ways that solutions will evolve. While policy decisions are the driving forces for technology development, the book was not designed to cover policy solutions.
Theis Adaptive Lean and Green (L&G) Manufacturing Approach in Productivity and Carbon Management Enhancement Wei D. Leong and Hon L. Lam Advances, Challenges and Opportunities of Li-Ion Batteries for Electric Vehicles Qianran He and Leon Shaw Charging Strategies for Electrified Transport Sheldon Williamson SECTION III. ELECTRICITY AND THE GRID The Role of Microgrids in Grid Decarbonization Mohsen Assadi Storage of Fluctuating Renewable Energy Peter Mitzey and Daniel Fozer Lithium-ion battery - future technology development driven by environmental impact Mihaela Buga, Adnana Spinu-Zaulet, and Alin Chitu Carbon Constrained Electricity Sector Planning with Multiple Objectives G.S.
Introductory Chapter. What key low-carbon technologies are needed to meet serious climate mitigation targets and what is their status Frank Princiotta SECTION I. BIOMASS SECTOR Biomass as A Source for Heat, Power, and Coproducts Viatcheslav Kafarov and A.M. Rosso-Ceron From Sugarcane to Bioethanol: The Brazilian Experience Romeu J. Daroda, Valnei S.
da Cunha Biomass in Regional and Local Context Michael Narodoslawki Prioritising Uses for Waste Biomass: A Case Study from British Columbia Roland Clift, Xiaotao Bi, Haoqi Wang, and Huimin Yin Industrial Oleochemicals From Used Cooking Oils (UCOs)- Sustainability Benefits and Challenges Alvaro Orjuela Advances in Carbon Capture through Thermochemical Conversion of Biomass Sonal Thengane Phytowaste Processing Josef Marousek Anaerobic Digestion for Energy Recovery and Carbon Management Akihisa Kita, Yutaka Nakashimada
and Shohei Riya Critical Aspects in Developing Sustainable Biorefinery Systems Based on Bioelectrochemical Technology With Carbon Dioxide Capture Jhuma Sadhukhan Synthesis of Regional Bioproducts Supply Networks Zan Zore, Lidija Cucek, and Zdravko Kravanja A Logistics Analysis for Advancing Carbon and Nutrient Recovery from Organic Waste Edgar Martin, Apoorva M. Sampat, Mariano Martin, Victor M. Zavala, and Gerardo J. Ruiz-Mercado Efficient and Low-Carbon Energy Solution Through Polygeneration with Biomass Kuntal Jana SECTION II. MANUFACTURING AND CONSTRUCTION (BATTERIES, BUILT ENVIRONMENT, AUTOMOTIVE, AND OTHER INDUSTRIES) Urban Carbon Management Strategies Joe Bozeman III and Thomas L.
Krishna Priya and Santanu Bandyopadhyay.
OCLC-licensed vendor bibliographic record.
Keywords: Carbon sequestration; SCIENCE / Environmental Science; TECHNOLOGY / Environmental Engineering & Technology